The evaluation of a national interprofessional palliative care workshop. Issue 5 (28th August 2015) - Kaasalainen, Sharon; Willison, Kathleen; Wickson-Griffiths, Abigail; Taniguchi, Alan
Abstract: The purpose of this study was to evaluate the impact of a palliative/end-of-life care workshop on students' perceptions of professional identity, team understanding, and their readiness for interprofessional education (IPE). A before-and-after design was used combining both qualitative and quantitative methods. A survey was completed by 25 undergraduate students from a variety of health care professional schools across Canada, both before and after they attended the five-day workshop. There was a significant increase in students' readiness for IPE, perceptions of professional identity, and team understanding after they attended the palliative care workshop. Students stated that learning about other professionals' backgrounds and becoming more sensitive to other team members and their scopes of practice helped change the way they would practice. The findings from this study will contribute to our understanding of student attitudes around IPE and palliative care.